Effect of ATC Automation Transparency on Acceptance of Resolution Advisories. Issue 19 (2019) - Jans, M.; Borst, C.; van Paassen, M.M.; Mulder, Max
Abstract: Air traffic controller workload is a bottleneck on air traffic growth, warranting automation solutions. This paper discusses the effect of transparency on the acceptance of resolution advisories generated by an adaptive automation tool. Two transparency types were tested in a between-subjects experiment ( n = 16). The first group worked with a display which explicitly presented the variables which the automation uses in its reasoning, while the second group worked with a display which allowed subjects to infer these variables, i.e., they were implicitly presented. Both incorporated a preview functionality, which allowed for a comparison of the automation resolution advisory and the controller solution. Results show no significant differences in acceptance of advisories, workload or frustration ratings between the transparency levels. Overall, the acceptance of automation advisories reduced (not significant). The group using the explicit transparency received more short-term collision alerts, and their automation was longer active. Neither group used the available preview functionality to its full extent.